Adaptation strategies of mexican lemon rootstock in response to iron deficiency - Maldonado-Torres, Ranferi (REVISTA TERRA LATINOAMERICANA, 2013)
In Mexico, alkaline or calcimorphic soils cause iron chlorosis in citrus species, affecting quality and production. Iron chlorosis control through the application of amendments to soil or plants is expensive and has had little success. The use of rootstock adapted to Fe stress conditions is a viable control alternative. In this study, the above mentioned strategy for developing tolerant Mexican lemon was assayed. Volkameriana (Citrus volkameriana Pasq), Macrophylla (Citrus macrophylla Wester) and Sour Orange (Citrus aurantium L.) rootstock were assessed under conditions of restricted Fe to select the varieties with better possibility of adaptation. Plants of each rootstock were grown for 2 months in nutritive solutions adjusted to pH 6.5 or 8 and two levels of Fe, 0 and 35 μM of Fe. Based on the quantity of absorbed anions and cations, active Fe concentration, OH- or H+ excretion, Fe reductive capacity of the roots and increment in the fresh weight, it was possible to conclude that Volkameriana and Macrophylla rootstocks had better adaptation strategies for acquiring Fe under conditions of deficiency.